2019
DOI: 10.1088/1757-899x/635/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Bending strength and Biological properties of PLA-HA composites for femoral canine bone fixation plate

Abstract: This research is based on the purposes to find suitable hot compression conditions of composites materials, also to optimize mechanical and biological properties of the plate specimen. The type of composites materials under this investigation are bio-polymers (polylactic acid: PLA) and bio-ceramic (Hydroxyapatite: HA). In this research, the term “The design of the experiment (DOE)” was implemented to find the relation between forming factors including the ratio of HA ratio, molding temperature, and molding pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…The bending power was investigated by a universal testing machine (UTC). As a conclusion to this research, the optimal bending conditions were found for plates with 5% HAP, 160 o C, 7 Mpa [260].…”
Section: Polymer / Ceramicssupporting
confidence: 52%
“…The bending power was investigated by a universal testing machine (UTC). As a conclusion to this research, the optimal bending conditions were found for plates with 5% HAP, 160 o C, 7 Mpa [260].…”
Section: Polymer / Ceramicssupporting
confidence: 52%
“…Additionally, the biocomposite created in this work has a higher flexural modulus than cancellous bone, which has a flexural modulus of 0.05–0.5 GPa [ 24 ]. The matrix’s overall modulus rises as a result of the incorporation of HA powder, since it slows down matrix phase movement around individual particles [ 56 ]. Apart from this, the flexural strength and flexural modulus produced by the biocomposite material increase with the amount of HA that is present.…”
Section: Resultsmentioning
confidence: 99%
“…In the permanent implantation, a firm chemical and biological bond formation at the junction of material surface and tissue interface. HA, 86,87 Polylactic acid (PLA)-HA, 164 Mg/fluorapatite, 102 silk fibroin/tannic acid/HA, 158 Sr/HA 165 , CNT/HA, 166 Sr/HA, 167,168 Ti/HA, 169 nano TiO 2 /HA, 170 SiO 2 /HA, 171 nano TiO 2 , 172 Si/biphasic calcium phosphate (BCP), 173 dicalcium silicate, 174 wollastonite, 175 and others 176…”
Section: Anti-bacterialmentioning
confidence: 99%
“…Must not elicit an adverse response or reaction to surrounding tissue, compatible to blood, and be integral to the body environment HA, 177 silk fibroin/tannic acid/HA, 158 Sr/HA, 165 Ti/HA, 178 TCP coatings, 179 mxene/HA, 90 collagen/HA, 88 PLA-HA, 164 silk fibroin/tannic acid/HA 158…”
Section: Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation